Bypass Inductor Type LCL Filter Parameter Optimization for Three-Level Grid-Connected Converter - Li , Ning; Zhang , Shiqian; Xiao , Zihan; An, Zhuoer; Zhang, Yan; Jiang, Lin (Frontiers in Energy Research, 2022)
In the application of the three-level grid-connected system, passive damping is the most common method to keep the LCL filter working stably. However, in the case of high power density, the low switching frequency of the grid-connected converter results in the complexity of filter parameter design, and the increase in passive components leads to lower equipment utilization efficiency. To solve the above problems, based on the optimization of resonant frequency and system loss, this study proposes a set of LCL filter parameter design processes of a three-level neutral point clamped (NPC) converter, which can switch components freely and is easy to achieve. This study explores the theoretical evidence and application value of the proposed design, considering the influence of the current ripple and the reactive power limit. The design adopts the improved passive damping method to select the appropriate inductance ratio and impedance ratio to make the resonance frequency of the whole system and the extra loss of the system smaller. The simulation and experiments show that compared with the conventional method, the improved design method reduces the current THD of the grid side by 1.5% and the damping resistance loss by 0.17%.